Rich: Life of Richard Burton - Bragg, Melvyn (Sevenoaks, Kent, UK Hodder and Stoughton, 1988)
This is the first biography of the actor, Richard Burton, to be supported by his own 300,000-word unpublished journals that cover the years of his marriage to Elizabeth Taylor, plus all his papers and unpublished memoirs of his adopted father. Many of those close to Burton have talked for the first time, including his daughter Kate, his elder sister Cis, who brought him up as her own after the death of his mother when he was two years old and the teacher Philip Burton who adopted him and gave him his name. Bragg has also had the benefit of conversations with actors and close friends, including Sir John Gielgud, Sir Michael Hordern, Lauren Bacall, Robert Hardy, John Neville, Emlyn Williams, John Le Carre and Alec Guinness. Here, the actor who was born Richard Jenkins, the twelfth child of a South Wales miner, stands revealed as never before, often in his own words. After a scholarship to Oxford, a brilliant career in the theatre, then Hollywood and films like "The Robe", his career blossomed with "Camelot" and "Cleopatra" after which he married co-star Elizabeth Taylor. Further films intervened, then, in quick succession, he divorced Elizabeth Taylor, married Suzy Hunt and re-married Taylor, divorced her and married Sally Burton. In the book he discusses marriage, women, his work, arthritis and addiction to drink, and also shows himself to be a fine descriptive writer and humourist with a love of literature. At the age of 56 he died in his sleep. Melvyn Bragg is the author of 13 novels; his non-fiction includes a study of Laurence Olivier, "Land of the Lakes" and "Speak for England".
Include Colored Illustrations and Index.
Keywords: Great Britain